DOP088 Microbial dysbiosis increases experimental colitis by interfering with short-chain fatty acid-dependent mucosal Reg3B expression. (16th January 2018) - Bajic, D; Su, A; Hillmer, K; Mejias-Luque, R; Bluemel, S; Docampo, M; Schmid, R; Schnabl, B; van den Brink, M; Gerhard, M; Stein-Thoeringer, C
Abstract: Background: The intestinal microbiota plays a major role in modulating the interaction between the gastrointestinal (GI) epithelium and the immune system. Increasing evidence suggests that inflammatory bowel disease is associated with gut microbiota disturbances. Such a microbial dysbiosis can affect immune signalling, but also gut epithelial homeostasis. However, the mechanisms of microbiota—epithelium interactions and their role in IBD development are barely understood. In the present study, we investigated the effects of antibiotic-induced gut microbiota disturbances as a model of microbial dysbiosis on intestinal epithelial responses and predisposition towards experimental colitis in laboratory mice. Methods: The present study used adult C57BL/6 mice and Reg3B knockout mice / littermates. Results: First, we treated mice with either a broad-spectrum antibiotic cocktail (AMT) or rifaximin (RFX) and observed a significant down-regulation of Reg3B as an antimicrobial protein in the intestinal mucosa (Figure A). As controls, germ-free mice had also had less Reg3B compared with conventional SPF mice. Reg3G as another member of the Reg family was not changed, but mucosal IL-22 was downregulated after AMT and in germ-free animals. 16S rRNA sequencing of RFX treated mice revealed rather microbiota shifts with reductions in Firmicutes, especially Clostridiales, than a broad antibacterial efficacy with the effect of a dysbiotic microbiome (Figure B). Investigating the pathophysiological relevance of this finding, we induced DSS colitis after RFX pretreatment and found a more severe colitis phenotype in RFX pretreated mice that was also confirmed in Reg3B knock-out animals (Figure C). Given that AMT and RFX target short-chain fatty acid (SCFA) producing bacteria we measured faecal SCFAs and found a reduction of predominantly propionate after RFX treatment (Figure D). Furthermore, mice lacking the SCFA receptor GPR43 and GPR109 displayed lower expression levels of gut mucosal Reg3B. In order to determine SCFA effects on epithelial Reg3B expression, we used the small intestinal organoid model and found propionate to regulate Reg3B expression via GPR43 (Figure E). Interestingly, colonising mice with an altered Schaedler flora producing propionate also induced intestinal Reg3B expression. Conclusions: In summary, we report a novel aspect of gut microbial dysbiosis with a consecutive SFCA deficiency which, in turn, leads to a reduction in Reg3B as an important antimicrobial, regenerative peptide in the gut mucosa and predisposition to colonic inflammation.